2020
DOI: 10.1002/sia.6910
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic transition in ultrathin Co sandwiched between Au layers in [Au (3.16 nm)/Co (1.5 nm)]x35/Si(100) multilayers

Abstract: The superparamagnetic to ferromagnetic transition in ultrathin Co layers has been investigated by systematic annealing of Co ultrathin layer sandwiched between a pair of Au layer in the [Au (3.16 nm)/Co (1.5 nm)]x35/Si(100) multilayers. Apart from this magnetic transition, annealing‐induced modifications in morphological and structural properties of this discontinuous island like Co ultrathin layer have also been investigated. The thickness and number of Co and Au layers were so chosen as to make a composition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…The overall results provide local structural information which is very useful in some technological importance as per application point of view. These results also support initial work performed on the sample as reported in our previous study [23].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The overall results provide local structural information which is very useful in some technological importance as per application point of view. These results also support initial work performed on the sample as reported in our previous study [23].…”
Section: Discussionsupporting
confidence: 92%
“…For present study, electron beam evaporation (EBE) technique under ultra-high vacuum environment is used to deposit multilayer thin film. In our previous study of this multilayer, we found magnetic phase transition and modification in structural and morphological properties as a function of annealing temperature [23]. On the basis of those results, in the present work, we have investigated the local structural information of the constituent elemental layers by X-ray absorption fine structure spectroscopy.…”
Section: Introductionmentioning
confidence: 71%
See 2 more Smart Citations